ANALISIS PENGARUH EKSPOR, IMPOR, DAN JUB DI INDONESIA TERHADAP KURS RUPIAH/USD - Frido Evindey Manihuruk; Dwi Silfani; Yohana Feby; Jonathan Marbun (Universitas Pasundan, 2023)
This study aims to analyze how exports, imports, and money supply in Indonesia affect the exchange rate of the rupiah against the US dollar. This quantitative research uses multiple linear regression with time series data from 2005 to 2022 obtained from BPS Indonesia. The results showed that exports have a negative and significant effect on the Rupiah exchange rate, while imports have no significant effect. The money supply has a positive and significant effect on the Rupiah exchange rate. The coefficient of determination of 88.85% indicates that the model can explain significant variations in the Rupiah exchange rate. This analysis focuses on the complex dynamics between exports, imports, money supply, and the Rupiah exchange rate. The results of this study are expected to provide more comprehensive insights into maintaining the stability of the Rupiah exchange rate and make a significant contribution to the development of national economic policy.